Mekanisme Pengelolaan dan Pengawasan Wakaf Saham Di Indonesia dan Malaysia - Finna Apriyani; Moh Khamim; Moh Taufik (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2024)
In Indonesia and Malaysia, a new form of waqf has developed, namely stock waqf. However, many people still do not know about the implementation of waqf shares. In the implementation of stock waqf, management and supervision challenges need to be overcome in order to increase its effectiveness. This study aims to (1) To examine the mechanism of management and supervision of waqf shares in Indonesia and Malaysia (2) To examine the differences and similarities of management and supervision in Indonesia and Malaysia. The type of research used is literature, the approach used is normative, data collection techniques using literature study analysis and using qualitative methods. The results of this research show that Indonesia and Malaysia in the implementation of waqf shares give their trust to nazhir as the only holder who manages and supervises waqf shares. in managing waqf shares, nazhir works with investment advisors. Based on the results of this research, it is expected that it will become information and input for students, academics, practitioners, and all parties who need information in the environment of the Faculty of Law, Pancasakti University Tegal and the wider community.